GESTATIONAL TROPHOBLASTIC DISEASE: CLASSIFICATION, EPIDEMIOLOGY AND PATHOGENESIS - A. G. Solopova; A. D. Makatsariya; E. S. Egorova; V. S. Moskvichyova; D. V. Mitryuk (IRBIS LLC, 2018)
Gestational trophoblastic disease (GTD) is a cumulative name of the diseases that occur in pregnant women as a result of abnormal trophoblast proliferation. It includes benign (full or partial hydatidiform mole) and malignant (so-called gestational trophoblastic neoplasias) diseases. Statistically, the incidence of hydatidiform mole varies from region to region. That may be due to either the ethnic factors or related to a specific diet, the quality of diagnosis, representatives of the statistical data and the lack of a uniform protocol of data registration.